한국 어린이 청소년의 알레르기질환에 관한 지역별 유병률에 대한 분석 - 이연희; 최재희; 박미란; 김지현; 김우경; 박용민; 이소연; 한만용; 채유미; 함명일; 이기재; 권호장; et al. (Allergy asthma & respiratory disease, 2015)
Purpose: This study aimed to analyze the prevalence of allergic diseases in Korean schoolchildren according to their residential areas in 2010. Methods: A nationwide, cross-sectional study was conducted in children aged 6–7 years (n=4,003) and adolescents aged 12–13 years (n=4,112) who were randomly selected. Demographic and disease-related information was obtained through a Korean version of ISAAC (International Study of Asthma and Allergies in Childhood) questionnaire, and skin prick tests for 18 inhalant allergens were performed. Results: There was statistically significant regional difference in the prevalence of allergic rhinitis (AR) (P<0.05). The regions with highest and lowest prevalence in 12- to 13-year-old children were as follows: Chungcheong and Honam in “Diagnosis of AR, ever” (33.7% vs. 24.5%), Jeju and Yeongnam in “Treatment of AR, last 12 months” (25.5% vs. 18.0%), Chungcheong and Yeongnam in “Rhinitis with sensitization” (31.6% vs. 23.6%). The regions with highest and lowest prevalence in 6–7 years old children were as follows: Yeongnam and Seoul in “Diagnosis of AR, ever” (42.1% vs. 31.0%), Yeongnam and Jeju in “Treatment of AR, last 12 months” (31.8% vs. 21.9%), Jeju and Seoul in “Rhinitis with sensitization” (26.0% vs. 18.4%). We also found a regional difference in inhalant allergens among the children with “rhinitis with sensitization”. Conclusion: The prevalence of AR in children differs according to residential areas in a nationwide survey in 2010 while there is no significant regional difference in the prevalence of asthma and AD. KCI Citation Count: 7